Pengaruh Pendidikan Kesehatan Terhadap Upaya Pencegahan Hipoglikemia Pada Pasien Diabetes Mellitus Di Ruang Intensive RSUD DR. Moewardi Surakarta Tahun 2016 - Arnis Prilli Dharmastuti; Dwi Ariani Sulistyowati (Poltekkes Kemenkes Surakarta, 2017)
Abstract: Hypoglycemia, Health Education, Knowledge, Patient. Hypoglycemia is one of the complications faced by people with diabetes mellitus, ie blood glucose levels fall below 50 to 60 mg / dl. Hypoglycemia may occur acutely, suddenly and can be life-threatening. Management of diabetes mellitus one of them is health education, especially about complications, namely Hypoglycemia. The objectives of this study were 1) to identify the level of knowledge of diabetes mellitus patients about prevention of hypoglycemia prior to health education 2) to identify the knowledge level of diabetes mellitus patients about hypoglycemia prevention after health education 3) to analyze knowledge change about prevention of hypoglycemia in patients with diabetes mellitus before and after the provision of health education in the intensive space of Dr Moewardi Hospital in 2016. This research type is experimental with pre-experimental design, variable approach using pre and post test designs method and data analysis used is Paired T-Test. The result of this research is there is influence of health education toward prevention effort of hypoglycemia in patient of diabetes mellitus in intensive room of Dr Moewardi Hospital 2016. This is proved by Paired T-Test test analysis on the value of knowledge before and after given health education obtained t count = -19,090, whereas t table value 2,042 so value -t arithmetic <-t table (-19,090 <-2,042) and sig. 0.000 (<0.05) then Ho is rejected and Ha accepted, meaning there is a significant difference between the value of knowledge before and after being given health education about hypoglycemia. There is an influence of health education on prevention of hypoglycemia in people with diabetes mellitus in intensive space Dr Moewardi Hospital in 2016.